A Feasibility Study on the Establishment of Pasta House at Diamond Road, Camarin, Caloocan City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Food is one of the basic needs of a person; it is something that is usually consume three times a day for a normal person. Through this basic necessity, researchers obtained the idea of introducing food with the twist to the market. Since pasta or what we called spaghetti became one of the traditional foods of the Filipino and believe that noodles or pasta makes life longer. Pasta House created a new variety of pasta sauce, which makes pasta tasty and delicious that contains much healthier nutrition content and it is a food that brings friends and family together to celebrate special event. The purpose of this study is to introduce a new variety of pasta sauce that would give satisfaction to pasta lovers. In order to determine if the business is feasible, the researchers conducted a survey through questionnaires to know whether the target market are willing to try a new variety of pasta sauce. The study also used financial analysis to determine the financial profitability of the business in the market. This study found out that the proposed business shows 90% of the respondents are willing to buy a new variety of pasta sauce. The price of the pasta lies with the respondents willing to invest to purchase. Social media is the most effective tools to reach out the target customer of Pasta House. The place where the business located was very accessible due to its most populated area within Caloocan City. Also, the proposed study can sustain its financial stability because of the level of profitability. The findings of the study confirmed that to become feasible, the business must offer additional unique quality of products and hire employee with sufficient qualification as the customer increases. The establishment of Pasta House will ensure market penetration since Filipinos are adventurous and always on the move to try something new.
Keywords: feasibility, establishment, pasta house